2012
DOI: 10.1007/bf03325328
|View full text |Cite
|
Sign up to set email alerts
|

Weight and body composition change over a six-week holiday period

Abstract: Change in weight and body composition was assessed over a six-week holiday period. Baseline testing occurred the Monday or Tuesday prior to Thanksgiving Day (November 24 or 25, 2008), and the post-holiday assessment was the Monday or Tuesday after New Year's Day (January 5 or 6, 2009). Thirteen men and 21 women ranging in age from 23-61 years completed the study. The majority of participants (24 of 34) perceived that they had gained weight, and four did gain ≥2 kg. However, despite some changes to dietary and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 8 publications
1
17
1
Order By: Relevance
“…In the other study on subjects a significant, though small, increase in waist circumference was observed [15]. …”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…In the other study on subjects a significant, though small, increase in waist circumference was observed [15]. …”
Section: Discussionmentioning
confidence: 93%
“…However, in another study conducted on students in University of Oklahoma-Norman campus; no significant weight gain was observed [4]. One more study showed that in overweight and obese people, weight gain is more significant than those with normal weight [4,15]. This study also found that subjects who have had weight gain, usually may return to their previous weight within a short time, but over time, their body fat increases without changing in BMI [4,15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations